Gordis epidemiology - Celentano, David D.; Gordis, Leon, 1934-2015.; Szklo, M. (Moyses) (Philadelphia, PA : Elsevier, 2019)
This bestselling text provides a solid introduction to basic epidemiologic principles as well as practical application in public health and clinical practice, highlighted by real-world examples throughout. New coverage includes expanded information on genetic epidemiology, epidemiology and public policy, and ethical and professional issues in epidemiology, providing a strong basis for understanding the role and importance of epidemiology in today's data-driven society. -- From publisher's description.
The dynamics of disease transmission -- The occurrence of disease: I. Disease surveillance and measures of morbidity -- The occurrence of disease:II. Morality and other measures of disease impact -- Assessing the validity and reliability of diagnostic and screening tests -- The natural history of disease: ways of expressing prognosis -- Observational studies -- Cohort studies -- Comparing cohort and case-control studies -- Assessing preventive and therapeutic measures: randomized trials -- Randomized trials: some further issues -- Estimating risk: is there an association? -- More on risk: estimating the potential for prevention -- From association to causation: deriving inferences from epidemiologic studies -- More on causal inference: bias, confounding, and interaction -- Identifying the roles of genetic and environmental factors in disease causation -- Using epidemiology to evaluate health services -- Epidemiologic approach to evaluating screening programs -- Epidemiology and public policy -- Ethical and professional issues in epidemiology.
Preceded by Epidemiology / Leon Gordis. Fifth edition. 2014.
Includes bibliographical references and index.
Keywords: Epidemiology; Epidemiologic Methods